Trade and Border Security as Political Issues in Canada - Cody, Howard (Maine Policy Review, 2003)
On February 5, 2003 the Maine International Trade Center and University of Maine Canadian American Center co-sponsored a day-long forum on the challenges and opportunities of free trade between Canada and the United States. In this article, edited from his presentation at this forum, Howard Cody begins with passage of the Free Trade Agreement and brings readers up to the present day, where trade and border security concerns have become inextricably combined. Cody argues that Canadians will not persuade Americans to distinguish between the two concerns and, consequently, that Canadians will eventually accept some sacrifice in national sovereignty in order to maintain the benefits of their current trade and investment relationship with the United States.